2018
DOI: 10.1002/jmv.25374
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection in patients with leprosy

Abstract: Leprosy patients may present with immune system impairment and have a higher hepatitis B virus (HBV) seroprevalence, justifying the investigation of occult HBV infection in these individuals. The aim of this study was to verify the frequency and the clinical factors associated with occult HBV infection in leprosy patients. Between 2015 and 2016, leprosy patients from a reference center in Brazil were interviewed to assess clinical data. Blood samples were collected for the screening of HBV serological markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The literature on leprosy viral co‐infections has focused on HIV, HTLV, hepatitis B, and hepatitis C 6–11 . Recently, we have also seen reports of cases of COVID‐19 in leprosy patients, in a context of strained healthcare services that most severely affected developing countries and delayed progress towards leprosy elimination 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on leprosy viral co‐infections has focused on HIV, HTLV, hepatitis B, and hepatitis C 6–11 . Recently, we have also seen reports of cases of COVID‐19 in leprosy patients, in a context of strained healthcare services that most severely affected developing countries and delayed progress towards leprosy elimination 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Co-infections can also pose additional challenges through drug interactions between leprosy multidrug therapy (MDT) and other antimicrobials. 5 The literature on leprosy viral co-infections has focused on HIV, HTLV, hepatitis B, and hepatitis C. [6][7][8][9][10][11] Recently, we have ª 2023 the International Society of Dermatology.…”
Section: Introductionmentioning
confidence: 99%
“…As an illustration, OBI prevalence among hemodialysis patients was 1.5% (Turkey), 24 0.5% (Iran), 25 0% (Germany), 26 1.3% (Japan), 27 and 0% (Italy) 28 ; in hemophilia patients was 1.73% in Pakistan, 29 9.3% in Iran, 30 and 0% in Polish 31 ; among thalassemia patients was 31.4% (India), 6 32.5% (Egypt), 5 and 0% (Iran) 13,14 ; in individuals with HCC was 30% (Japan), 32 38.5% (Korea), 33 50% (Egypt), 34 and 70.4% (China) 35 ; among blood donors in different parts of the world was 3.7% (Egypt), 36 4.71% (India), 37 1.98% (Colombia), 38 0.3% (Lebanon), 39 0% (Iran), 8 and 7.4% (Libya). 40 OBI also has been found in patients with leprosy in Brazil (5.3%), 41 individuals suffering from hyperlipidemia in China (9.5%), 42 patients with primary glomerulopathy (3%) and lupus nephritis (13.3%) in Iran, 43 and among ART (antiretroviral therapy) naïve HIV-seropositive individuals in Mozambique (8.3%). 44 Despite other studies in which the frequency of OBI among Iranian BTM patients was0%, 13,14 data obtained in this study showed that one of 86 BTM patients, who were negative for HBsAg, had OBI (1.16%).…”
Section: Resultsmentioning
confidence: 97%
“…According to previous studies, HBV gene mutation, immunosuppression and insufficient hepatitis B detection technology are the main reasons [7,8]. From the perspective of gene mutation, HBV is more prone to gene invariability, and the mutation region is mainly the envelope protein S gene region, core promoter [9], and the core hydrophilic region MHR of the S gene region is the most important mutation site [10,11]. The mutation frequency in this region is high, which will lead to the binding of antibody and antigen during HBsAg detection.…”
Section: Introductionmentioning
confidence: 99%